Experimental and computational fluid-structure interaction analysis and optimization of deep-V planing-hull grillage panels subject to slamming loads – Part I: Regular waves - Diez, Matteo; Lee, Evan J.; Harrison, Emily L.; Powers, Ann Marie R.; Snyder, Lawrence A.; Jiang, Minyee J.; Bay, Raymond J.; Lewis, Richard R.; Kubina, Eric R.; Mucha, Philipp; Stern, Frederick (Marine structures, 2022)
The paper presents the multidisciplinary design optimization (MDO) of a deep-V planing-hull grillage panel subject to slamming loads in regular waves. Namely, fluid structure interaction (FSI) experiments, computations, and MDO are presented and discussed for a bottom-panel grillage of a high-speed Generic Prismatic Planing Hull in regular waves. Computations are performed via one- and tightly coupled two-way computational fluid and structural dynamics (CFD/CSD) using unsteady Reynolds-averaged Navier-Stokes equation solvers to compute the hydrodynamic loads. The structural assessment of the original/traditional grillage is performed using a fully parametric finite element (FE) model, showing the significant effects of the FE boundary conditions on the structural response. Firstly, an equivalent static and uniform load is identified via CFD and applied during optimization using two design spaces. The selected optimized design provides a grillage-weight reduction of 35% and an overall factor of safety equal to 1.72. The optimized design presents variations of stiffeners dimensions across the grillage with the largest stiffener at the middle, distributing the stress more uniformly among the stiffeners. The effects of one-versus two-way coupling are negligible for both the original/traditional and optimized grillages (as per the hydroelasticity factor R), whereas the effects of FE boundary conditions on the analysis and optimization outcomes are significant, confirming the need for proper calibration of the FE model in FSI and MDO studies. Secondly, MDO is performed with a dynamic load applied via one-way coupling FSI. An additional 5% weight reduction is identified, achieving a 40% weight reduction compared to the traditional grillage. The optimal design presents the largest stiffener close to the keel, which is significantly different than the design obtained for uniform/static load. Comparison of computational and experimental data is very good, indicating that the accuracy of CFD, rigid-body motions, CSD, and FSI is overall satisfactory. Overall, the development of the computational tools is successful, and the computational/optimization capabilities are demonstrated via comparison with experimental data for both the original/traditional and static-load optimized grillages. •FSI experiments, computations, and MDO are shown for high-speed GPPH panels in regular waves.•Both static/uniform and dynamic load optimization approaches are presented and discussed.•A 40% weight reduction is achieved.•Validation of computations versus experiments (both original and optimized designs) is satisfactory.